ANALYSIS OF COMMON SIZE AND NETWORK CAPITAL TO MEASURE FINANCIAL PERFORMANCE IN BADAN USAHA MILIK DESA (BUMDes) DISTRICT CIAWI, TASIKMALAYA - Asep Saeful Falah; Lati Sari Dewi (Universitas Perjuangan Tasikmalaya, 2023)
The Common Size and Working Capital analysis is useful for measuring whether or not the company's financial performance is good. This research was conducted to measure the financial performance of BUMDes in Ciawi District. The method used in this research is descriptive quantitative method. From the results of the Common Size analysis and working capital of BUMDes Jaya Rahayu, there is a decline in the financial performance of BUMDes Jaya Rahayu to the point of causing continuous losses and in 2021 experiencing a very large deficit of 993.15% and the capital turnover of BUMDes Jaya Rahayu from 2020-2021 decreased by 7.47%. In the results of the common size and working capital analysis, there was an increase in the financial performance of BUMDes Warga Mandiri seen from an increase in profit to 2.34% and experienced a surplus of 71.5% and 51.9% in 2020 and 2021 as well as Working Capital Turnover in BUMDes Warga Mandiri experienced an increase of 0.057 times. In the results of the comparative analysis there is a significant difference, namely BUMDes Jaya Rahayu has a fantastic operational cost of 73.6% in 2020 and 1,061.7% in 2021.